Knowledge on Reproductive Health Issues Among the Unmarried Adolescent Girls - Nasreen Akther; Nadia Begum; Shahanaz Chowdhury; Sabiha Sultana (Tehran University of Medical Sciences, 2012)
Objective: To assess the level of knowledge of the adolescent girls regarding reproductive health issues. Materials and methods: A cross sectional descriptive type of study was carried out among 150 unmarried adolescent girls of Vashantek slum in Dhaka city by face to face interview using a semistructured questionnaire from January to June 2008. Results: The mean age of the respondents were 16.4±2.9 years ranging from 10-19 years. Out of 150 respondents, 130 had history of menstruation and their median age of menarche was 13 years. The correct knowledge was high among the adolescent having secondary level of education than the SSC and above or primary level of education and the difference was statistically significant (p<0.05). About three-fourths of the respondents had sufficient knowledge about hygienic menstrual practice. Majority of the girls could mention the legal age of marriage. Regarding the demerits of early marriage, majority mentioned some of the demerits but not all. Three-fifths of the respondents had no knowledge on importance of family planning and regarding the methods of family planning, majority of them had no knowledge. Majority of the respondents heard the disease AIDS but regarding the knowledge on causative agent half of them had no knowledge. More than two-fifths had no knowledge on mode of transmission of AIDS. It was also found that majority of the  respondents had no knowledge on symptoms of AIDS and three-fifths had no knowledge on prevention of AIDS. Conclusion: So formal, informal and special educational program may be taken to educate the adolescent girls on reproductive health issues and government should be more concerned about this.